History of Neurosurgery at The Royal Free Hospital in London. (June 2014) - Pulhorn, Heinke; Bradford, Robert; Dorward, Neil; Murphy, Mary; Shieff, Colin; Thorne, Lewis; Maurice-Williams, Robert
Abstract The recent move of the neurosurgical services from The Royal Free London NHS Foundation Trust in Hampstead to The National Hospital for Neurology and Neurosurgery at Queen Square signified the end of an era of neurosurgery in North London. It also represents also another chapter in the history of the remarkable North London hospital that is The Royal Free Hospital. This short article looks at the history of the Department of Neurosurgery at The Royal Free Hospital and the factors contributing to the reorganisation of neurosurgical services in North London.